Marginalization of fishing communities during gentrification: Access to housing and livelihood in Teluknaga, Indonesia - Rini Naibaho; Megawati Rusdianto; Jely Agri Famela; Sahat Pandapotan Nainggolan (SIMULACRA: JURNAL SOSIOLOGI, 2026)
Gentrification is characterized by the influx of high-income residents into areas that were originally low-value. Previous studies have stated that gentrification evictions, identity crises, and increased living costs, as well as causing a dramatic transition with the emergence of gated communities that separate wealthy newcomers from the original residents. This study examines the marginalization of access experienced by fishing communities as a result of gentrification in Kampung Muara, Teluknaga District, Tangerang Regency. This study uses a qualitative approach, with primary data collected through observation and interviews and secondary data collected from related studies. The results show that gentrification in Kampung Muara has marginalized the fishing community through evictions and increased vulnerability. Although the community staged protests, their efforts were unsuccessful. An interesting finding of this study is the land acquisition strategy used by developers: they first buy land at the beginning and end of the village and then target the middle. This pattern creates the middle area to eventually sell their land, even if the compensation is below the previous market value. In practical terms, this study recommends strengthening protections for the rights of fishing communities in practice. Theoretically, a study of gentrification focusing on fishing communities is recommended.